Complexity, Pedagogy and Aristotelian Metaphysics - Giuseppe Mari (Universidad de Navarra, 2009)
In Italy a large number of Pedagogy scholars are interested in Aristotle's Philosophy because the Stagirite starts from the real situation in order to devise his metaphysical theories. This attitude is close to the Paradigm of Complexity, common today from the epistemological point of view. This article, after a brief reconstruction of the Paradigm of Complexity, focuses on Aristotle's doctrine of the multivocity of being, interpreting it as a good theory to support the Paradigm of Educational Sciences in contemporary Pedagogical thought.